Computer organization and design : the hardware software interface - Patterson, David A.
This version of 'Computer Organization and Design' features the RISC-V open source instruction set architecture, the first open-source architecture designed to be used in modern computing environments such as cloud computing, mobile devices, and other embedded systems. Improvements to the new second edition, including new sections in each chapter on Domain Specific Architectures (DSA) and updates of all of the real-world examples in the book, keep it fresh and relevant for a new generation of students